(3GdJShjb (B:s (3eYQaI GdShb hGdeSJgdcjf(B-(3ef GdOQGSI GdJShjbjI Edi GdNjGQGJ GdESJQGJjLjI(B-(3GdeRjL GdJShjbj (B/s - (3bjh, cGJQjfs; (3hGTO, hQOjI s ((3HjQhJ(B: s (3eLO GdeDSSI GdLGeYjI ddOQGSGJ hGdfTQ(B, s, 2008)
(3eONd Edi GdJShjb,GdShb hGdaYGdjGJ,Sdhc GdeSJgdc,GdOQGSI GdJShjbjI,GdJLRFI GdJShjbjI,GdESJgOGa hJMOjO GdehbY,SjGSI GdefJL,SjGSI GdeGQcI,SjGSI GdJSYjQ,SjGSI GdEJUGd hJfejI GdeHjYGJ,GdJhRjYs
(3HHdjhZQGajG(B:(3U U(B.305-308s
Keywords: (3GdJShjbs